Arte e sustentabilidade: uma leitura sobre a temática ambiental na obra de três artistas do cenário tocantinense - Magalhães, Walena de Almeida Marçal (Universidade Federal do Tocantins, 2016)
The Art of Sustainability: A Reading on Environmental Themes [motifs] from the Conceptional Sphere of Three Artists of the Tocantins Region. This study examines the panoramic intersection of the visual arts and the environment in the state of Tocantins, Brazil by observing the principal works of three artists of the region, analyzing and categorizing those with regard to their depiction and treatment of environmental and sustainability concerns, and probing the resources utilized in treating those themes. The conceptual framework toward that end encompasses the categories of "Art," "Sustainability" and correlated terms to demonstrate how works of art are representations and how freedom has given rise in contemporary art to the existence and development of movements with that interdisciplinary bent. The works and craft of Sandra Oliveira, Claudio Montanari and Marcos Dutra reveal artistic commitment to environmental concerns and substantiate how art can be interfaced with environmental discourse and contribute to the sustainability of the planet. The methodology includes field research utilizing analysis of discourse and content, "reading" the art works like a "text." The final aspect is to propose future research and activities that might propagate and supplement the interface between the two areas examined here, to kindle further contributions built on this framework, and to spur greater artistic production in this vein, particularly in the states of the Brazilian Amazon region